Dynamics of the plasma electrolytic polishing process of austenitic steel AISI 304 in a solution of ammonium sulfate - Mihal, O.V.; Moroz, O.V.; Starovoytov, R.I.; Lytovchenko, S.V.; Mazilin, B.A.; Iliushyn, L.O. (Вопросы атомной науки и техники, 2018)
Modern industrial technological processes together with scientific research activities require the special
preparation of the metal surfaces for the further treatments. At present time the variety of techniques for the metal
surface processing exist. Among them one could outline the plasma electrolytic polishing (PEP) due to its capability
together with the decoration effect to enhance the surface properties. Despite the number of papers published in
different journals the PEP stays an innovative surface treatment and requires further study to obtain optimal
processing regimes. In present contribution the experimental study of PEP process dynamics with further numerical
analysis of physical aspects for steel AISI 304 in a solution of ammonium sulfate with the mass fraction of 3% is
given. After analyzing the experimental results the optimal PEP regime for the steel AISI 304 in a solution of
ammonium sulfate with the mass fraction of 3% was identified. Сучасні виробнично-технологічні процеси разом з науково-дослідницькою діяльністю вимагають
спеціальної підготовки металевих поверхонь для подальшої обробки. На цей час існує безліч методів
обробки поверхні металу. Серед них можна виділити плазмове електролітичне полірування (PEP) через його
здатність покращення властивостей поверхні з ефектом полірування. Незважаючи на число публікацій в
різних журналах, PEP залишається інноваційним методом обробки поверхні та потребує подальшого
вивчення для отримання оптимальних параметрів полірування. У цій статті представлено експериментальне
дослідження динаміки процесу PEP з подальшим чисельним аналізом фізичних властивостей сталі AISI 304
у розчині сульфату амонію з масовою часткою 3%. Після аналізу експериментальних результатів було
визначено оптимальний режим PEP для сталі AISI 304 у розчині сульфату амонію з масовою часткою 3%. Современные производственно-технологические процессы вместе с научно-исследовательской
деятельностью требуют специальной подготовки металлических поверхностей для дальнейшей обработки. В
настоящее время существует множество методов обработки поверхности металла. Среди них можно
выделить плазменную электролитическую полировку (PEP) из-за ее способности улучшения свойств
поверхности с эффектом полировки. Несмотря на число публикаций в разных журналах, PEP остается
инновационным методом обработки поверхности и требует дальнейшего изучения для получения
оптимальных режимов полирования. В данной статье представлено экспериментальное исследование
динамики процесса PEP с дальнейшим численным анализом физических свойств стали AISI 304 в растворе
сульфата аммония с массовой долей 3%. После анализа экспериментальных результатов был определен
оптимальный режим PEP для стали AISI 304 в растворе сульфата аммония с массовой долей 3%.